A critical evaluation of systematic reviews assessing the effect of chronic physical activity on academic achievement, cognition and the brain in children and adolescents: a systematic review - Wassenaar, TM; Williamson, W; Johansen-Berg, H; Dawes, H; Roberts, N; Foster, C; Sexton, CE (BioMed Central, 2020)
Background International and national committees have started to evaluate the evidence for the effects of physical activity on neurocognitive health in childhood and adolescence to inform policy. Despite an increasing body of evidence, such reports have shown mixed conclusions. We aimed to critically evaluate and synthesise the evidence for the effects of chronic physical activity on academic achievement, cognitive performance and the brain in children and adolescents in order to guide future research and inform policy. Methods MedLine, Embase, PsycINFO, Cochrane Library, Web of Science, and ERIC electronic databases were searched from inception to February 6th, 2019. Articles were considered eligible for inclusion if they were systematic reviews with or without meta-analysis, published in peer-reviewed (English) journals. Reviews had to be on school-aged children and/or adolescents that reported on the effects of chronic physical activity or exercise interventions, with cognitive markers, academic achievement or brain markers as outcomes. Reviews were selected independently by two authors and data were extracted using a pre-designed data extraction template. The quality of reviews was assessed using AMSTAR-2 criteria. Results Of 908 retrieved, non-duplicated articles, 19 systematic reviews met inclusion criteria. One high-quality review reported inconsistent evidence for physical activity-related effects on cognitive- and academic performance in obese or overweight children and adolescents. Eighteen (critically) low-quality reviews presented mixed favourable and null effects, with meta-analyses showing small effect sizes (0.1–0.3) and high heterogeneity. Low-quality reviews suggested physical activity-related brain changes, but lacked an interpretation of these findings. Systematic reviews varied widely in their evidence synthesis, rarely took intervention characteristics (e.g. dose), intervention fidelity or study quality into account and suspected publication bias. Reviews consistently reported that there is a lack of high-quality studies, of studies that include brain imaging outcomes, and of studies that include adolescents or are conducted in South American and African countries. Conclusions Inconsistent evidence exists for chronic physical activity-related effects on cognitive-, academic-, and brain outcomes. The field needs to refocus its efforts towards improving study quality, transparency of reporting and dissemination, and is urged to differentiate between intervention characteristics for its findings to have a meaningful impact on policy.